Vision of the Community Health Agent on the follow-up of the Newborn (Research, Society and Development, 2022)
The neonatal period, corresponding to the 28th day of the baby's life, according to the Ministry of Health, is a period in which the newborn is exposed to physical and socioeconomic risk factors. Aiming at this, the Government instituted actions for health promotion and prevention aimed at NBs and one of them is focused on the first home visit of the Community Health Agent, which must be carried out until the fifth day of life, offering crucial guidelines for healthy development. the same. In this study we will address the knowledge and experiences related to the first visit of the newborn, aiming to know which actions and health promotions the ACS professional intends for users in this age group. The research was carried out in an observational, descriptive way, with a qualitative approach, through Bardin's theory, at the Sacramenta II Family Health Unit, in Belém-PA. It was evidenced that more than half of the professionals do not report difficulties during the handling with the newborn and their families due to the bond of trust created, however, they demonstrate a lack of knowledge about their skills and the need for training and planning.